REALIZATION OF INTERDISCIPLINARY COMMUNICATIONS OF FUNDAMENTAL DISCIPLINES AND DISCIPLINES OF MATHEMATICAL CYCLE IN THE PREPARATION OF FUTURE PROGRAMMERS - Lvov, M.; Grigorieva, V. (Journal of Information Technologies in Education (ITE), 2016)
The article is devoted to interdisciplinary communication in the process of preparation of the future programmers and implementation of the basic principles of these relations in the study of disciplines of professional and practical training and math courses. The article deals with the role of interdisciplinary connections, as well as their function and significance for the formation of cognitive activity, independence and positive learning motivation. The focus is on methodological aspects of realization of interdisciplinary communications at studying basic disciplines of training future programmers and disciplines of mathematical cycle. In particular,the issues of realization of interdisciplinary communications during the study such disciplines as "Computer graphics, computational geometry," "Basics of algorithms and programming","Programming Technologies" and the course "Analytical geometry and linear algebra", which included in to normative part of the training of programmers. This article describes the theoretical aspects of the implementation of interdisciplinary connections in the study of these disciplines, as well as examples of practical tasks with which these relationships can be implemented most effectively during training.